The determinants of the usefulness of online reviews in the tourist offer selection - Sofronijević, Katarina; Kocić, Milan (Hotel and Tourism Management, 2022)
The dynamics of the development of tourism sector is reflected, among other things, in the fact that an increasing number of tourists choose an offer based on online reviews. Although it is true that due to the intensive development of communication via the Internet, online reviews are one of the dominant sources of information, their level of perceived usefulness may differ. The aim of the research is to examine the extent to which textual comments, photos and ratings of tourist offers determine the usefulness of online reviews. In order to analyze the results, we used exploratory factor analysis. Moreover, by using regression analysis, it was confirmed that usefulness affects the level of trust in online reviews, as well as that trust has implications for the intention to purchase a tourist offer. Finally, we came to conclusions that may have numerous implications for the decisions of marketing managers in the field of tourism.